EU structural funds and growth prospects: A sobering experience - Philipp Breidenbach (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
New research shows that regional funding of the European Union - currently amounting to 450 billion Euros - has no positive effect on economic growth. - In the financial framework period of 2014 to 2020, for the first time the European Structural Funds represent the main share of the European Union's (EU) budget. Previous evaluations on the funding's effectiveness reveal contradicting results. A new and robust RWI study does not find any positive effects of the program on economic growth. In fact, impacts indicate that highly funded regions might have to overcome structural problems first before growth programs can take effect. Also, a high intensity of funding in the immediate regional neighborhood has a strongly negative influence on a region's growth prospects.
Keywords: 330